Induced pluripotent stem cell–related approaches to generate dopaminergic neurons for Parkinson’s disease - Ling-Xiao Yi; Hui Ren Woon; Genevieve Saw; Li Zeng; Eng King Tan; Zhi Dong Zhou (Neural Regeneration Research)
The progressive loss of dopaminergic neurons in affected patient brains is one of the pathological features of Parkinson’s disease, the second most common human neurodegenerative disease. Although the detailed pathogenesis accounting for dopaminergic neuron degeneration in Parkinson’s disease is still unclear, the advancement of stem cell approaches has shown promise for Parkinson’s disease research and therapy. The induced pluripotent stem cells have been commonly used to generate dopaminergic neurons, which has provided valuable insights to improve our understanding of Parkinson’s disease pathogenesis and contributed to anti-Parkinson’s disease therapies. The current review discusses the practical approaches and potential applications of induced pluripotent stem cell techniques for generating and differentiating dopaminergic neurons from induced pluripotent stem cells. The benefits of induced pluripotent stem cell-based research are highlighted. Various dopaminergic neuron differentiation protocols from induced pluripotent stem cells are compared. The emerging three-dimension-based brain organoid models compared with conventional two-dimensional cell culture are evaluated. Finally, limitations, challenges, and future directions of induced pluripotent stem cell–based approaches are analyzed and proposed, which will be significant to the future application of induced pluripotent stem cell–related techniques for Parkinson’s disease.